Konsep Psikoterapi Sufistik Untuk Pembinaan Kesehatan Mental - Dianing Prafitri (Esoterik: Jurnal Akhlak dan Tasawuf, 2018)
Sufistic psychotherapy that is intended in writing this article is a treatment that nuanced Sufism with the aim to realize a healthy bermental human being. In this study primary sources consisted of literature that directly related to research variables, namely various data about sufistik psychotherapy and mental health. While the secondary sources, namely data related to this research one of them about psychotherapy. This research approach using psychological approach. The psychological approach used as the basis for this research is Sufistic psychotherapy. If faith gave birth to theology of science / kalam, Islam gave birth to the science of shari'ah, then Islam gave birth to the science of akhlaq or tasawuf. His theories are tested in the context of therapeutic psychology, workshops in individual development, individual experimentation by inducing altered state of consciousness eg by worship, meditation, hypnosis, etc., including dhikr. The results of this study, seen that can be used as a cure for mental illness, so as to nurture individuals to achieve mental health.